Educação e família: uma relação indispensável para o desenvolvimento das crianças até seis anos de idade - Reinke, Sonia Heimann (2006)
An analysis of the relationship between education and family seeking to the child's integral education up to six years of age. The first part detaches the importance of the family in the education and your influence in the children's life, considering the different forms that the family presents and your transformation process and adaptation by the challenges and crises that settle. The children's needs and your development are analyzed starting from some theories of the development. In the second chapter, they come some occasional crises and critical situations that the family can face which cause great impact in the children's development and that need to be worked. To conclude this chapter, it is referred to the public politics and your impact on the families, questioning your effectiveness and, consequently your contribution for a life more worthy of the children and your families. In the last chapter a challenge is thrown to the families so that they take the responsibility for your children's education. Besides, they come several practices for the education in the family, emphasizing the need of a partnership relationship with the school, the church and the State, so that, all together ones, in the fight for the dignity, they can offer to the children an education that qualifies for the life, that transforms the reality, that opens horizons and it swallows the hope of a better future.